Features of speech in German and US-American mother–toddler dyads during toy play and book-reading. Issue 1 (16th January 2020) - DOERING, Elena; SCHLUTER, Kevin; SUCHODOLETZ, Antje von
Abstract: Previous research indicates that features of speech during mother–toddler interactions are dependent on the situational context. In this study, we explored language samples of 69 mother–toddler dyads collected during standardized toy play and book-reading situations across two countries, Germany and the United States (US). The results showed that features of speech differed across situational contexts. However, situational differences were mostly found among the sample from the US but not from Germany. Few significant associations between mothers' and toddlers' language variables were found. Findings are discussed with regard to variations in language across situations and countries.